Selection of Bacterial Strains for Control of Root-Knot Disease Caused by Meloidogyne incognita - Varvara D. Migunova; Natalia S. Tomashevich; Alena N. Konrat; Svetlana V. Lychagina; Valentina M. Dubyaga; Trifone D’Addabbo; Nicola Sasanelli; Anzhela M. Asaturova (Microorganisms, 2021)
Root-knot disease caused by Meloidogyne incognita leads to significant crop yield losses that may be aggravated by the association with pathogenic fungi and bacteria. Biological agents can be effectively used against the complex disease of root-knot nematode and pathogenic fungi. In this study, 35 bacterial strains were analyzed for their in vitro nematicidal, antagonistic and growth stimulation activities. Based on results from the in vitro assays, grow-box experiments on tomato and cucumber were carried out with the strain BZR 86 of Bacillus velezensis applied at different concentrations. Effects of B. velezensis BZR 86 on the development of root-knot disease were evaluated by recording root gall index, number of galls and number of eggs in egg masses. Application of B. velezensis BZR 86 noticeably decreased the development of root-knot disease on tomato and cucumber plants, as well as significantly increased growth and biomass of cucumber plants in accordance with bacterial concentration. This study seems to demonstrate that strain B. velezensis BZR 86 could be an additional tool for an environmentally safe control of root-knot disease on horticultural crops.